Antimycobacterial and Nitric Oxide Production Inhibitory Activities of Ocotea notata from Brazilian Restinga - Isabela Francisca Borges Costa; Sanderson Dias Calixto; Marlon Heggdorne de Araujo; Tatiana Ungaretti Paleo Konno; Luzineide Wanderley Tinoco; Denise Oliveira Guimarães; Elena B. Lasunskaia; Ivana Ramos Correa Leal; Michelle Frazão Muzitano (The Scientific World Journal)
The genus Ocotea (Lauraceae) is distributed mainly in tropical and subtropical regions. Some species of this genus as O. puberula and O. quixos have been described in the literature, showing antibacterial activity. And Ocotea macrophylla showed anti-inflammatory activity with inhibition of COX-1, COX-2, and LOX-5. The purpose of this study was the phytochemical investigation of the plant species Ocotea notata from Restinga Jurubatiba National Park, Macaé, RJ, Brazil, and the search for antimycobacterial fractions and compounds. The crude extract was evaluated for antimycobacterial activity and presented 95.75±2.53% of growth inhibition at 100 µg/mL. Then, it was subjected to a liquid-liquid partition and subsequently was chemically investigated by HPLC, revealing the major presence of flavonoids. In this process the partition fractions hexane, ethyl acetate, and butanol are shown to be promising in the antimycobacterial assay. In addition, ethyl acetate fraction was chromatographed and afforded two flavonoids identified by MS and NMR as afzelin and isoquercitrin. The isolated flavonoids afzelin and isoquercitrin were evaluated for their antimycobacterial activity and for their ability to inhibit NO production by macrophages stimulated by LPS; both flavonoids isoquercitrin (Acet22) and afzelin (Acet32) were able to inhibit the production of NO by macrophages. The calculated IC50 of Acet22 and Acet32 was 1.03 and 0.85 µg/mL, respectively.